Predictive factors for self-medication during pregnancy (Research, Society and Development, 2020)
Medicalization during pregnancy, associated with the irrational use of medications, establishes high-risk behavior, since no medication is free of toxicity to the mother or fetus and must be seen as a public health problem. This study aimed to analyze in the scientific literature the predictive factors for self-medication during pregnancy. This work is a bibliographic review of the narrative type, where the selection of the studies was carried out in the online databases:); Latin American and Caribbean Literature in Health Sciences (LILACS), Scientific Electronic Library Online (SciELO) and Virtual Health Library (VHL), between the years 2009 to 2019. After filtering the articles, we obtained 01 article in the LILACS database, 05 articles in the SciELO database and 03 articles in the VHL database, which resulted in a total of 09 articles. Studies have shown that the first trimester of pregnancy is a critical period for exposure to drugs due to the formation of basically all the anatomical and physiological structures of the fetus, which can cause malformations and miscarriage. Self-medication is a current practice in Brazil and mainly involves the use of non-prescription drugs, and users should be aware of their possible risks.